2018
DOI: 10.1016/j.alit.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The global development and clinical efficacy of sublingual tablet immunotherapy for allergic diseases

Abstract: Allergy immunotherapy (AIT) is a treatment option for respiratory allergy that is complementary to pharmacotherapy, with a distinct mechanism of action. Alternative methods to subcutaneous administration of AIT that enable patients to safely self-administer AIT is considered an unmet clinical need. The sublingual immunotherapy tablet (SLIT-tablet) is an orally disintegrating pharmaceutical formulation (oral lyophilisate) containing standardized allergens. SLIT-tablets have been developed for sublingual immunot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 59 publications
1
31
0
1
Order By: Relevance
“…For regulatory reasons, clinical trials on pediatric patients are performed after first evidence in adults; thus, the evidence arising from pediatric trials is lower. However, combined experience performed on the trials for grass sublingual tablet registration both in adults and in children supports similar clinical effect and underlying mechanisms …”
Section: Prescribing Immunotherapy To Pollens In Children: Influencmentioning
confidence: 99%
“…For regulatory reasons, clinical trials on pediatric patients are performed after first evidence in adults; thus, the evidence arising from pediatric trials is lower. However, combined experience performed on the trials for grass sublingual tablet registration both in adults and in children supports similar clinical effect and underlying mechanisms …”
Section: Prescribing Immunotherapy To Pollens In Children: Influencmentioning
confidence: 99%
“…13 (11)(12)(13)(14) 15 (14)(15)(16) < 0.001 11 (10)(11)(12)(13)(14)(15) 12 (9)(10)(11)(12)(13)(14)(15)(16) 0.5…”
Section: Discussionunclassified
“…Different formulations of allergens have been developed as alternatives to SCIT, such as the sublingual immunotherapy tablet (SLIT-tablet). Particularly SLIT-tablets may be beneficial for children who are scared of injections and needles [14]. The SLIT-tablets have been developed for the treatment of grass pollen-induced AR and HDMinduced AR but the allergen content and dosing have not been standardized to date.…”
Section: General Methods and Novel Approaches Of Administrationmentioning
confidence: 99%
“…The varied content among different products also affects the guidelines [15]. In addition, a limitation of SLIT tablet occurs from its ingredient which consists of only one antigen [14]. It has been recently demonstrated that pharmaceutical SLIT-tablet formulations are also important and affects the efficacy with which allergen has delivered from the dry state of the tablet into a soluble form [16].…”
Section: General Methods and Novel Approaches Of Administrationmentioning
confidence: 99%
See 1 more Smart Citation